3D Printing Fiber Electrodes for an All‐Fiber Integrated Electronic Device via Hybridization of an Asymmetric Supercapacitor and a Temperature Sensor. Issue 11 (25th September 2018) - Zhao, Jingxin; Zhang, Yan; Huang, Yinan; Xie, Jixun; Zhao, Xiaoxin; Li, Chaowei; Qu, Jingyi; Zhang, Qichong; Sun, Juan; He, Bing; Li, Qiulong; Lu, Conghua; et al.
Abstract: Wearable fiber‐shaped electronic devices have drawn abundant attention in scientific research fields, and tremendous efforts are dedicated to the development of various fiber‐shaped devices that possess sufficient flexibility. However, most studies suffer from persistent limitations in fabrication cost, efficiency, the preparation procedure, and scalability that impede their practical application in flexible and wearable fields. In this study, a simple, low‐cost 3D printing method capable of high manufacturing efficiency, scalability, and complexity capability to fabricate a fiber‐shaped integrated device that combines printed fiber‐shaped temperature sensors (FTSs) with printed fiber‐shaped asymmetric supercapacitors (FASCs) is developed. The FASCs device can provide stable output power to FTSs. Moreover, the temperature responsivity of the integrated device is 1.95% °C −1 . Abstract : 3D printing of fiber electrodes for an all‐fiber integrated electronic device via hybridization of an asymmetric supercapacitor and a temperature sensor is reported. A self‐energy monitoring system is developed that exhibits excellent electrochemical performance and rapid temperature response.